2016
DOI: 10.1016/j.mayocp.2016.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain and Mental Health Disorders

Abstract: Chronic pain and mental health disorders are common in the general population, and epidemiological studies suggest that a bidirectional relationship exists between these 2 conditions. The observations from functional imaging studies suggest that this bidirectional relationship is due in part to shared neural mechanisms. In addition to depression, anxiety, and substance use disorders, individuals with chronic pain are at risk of other mental health problems including suicide and cigarette smoking and many have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
188
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 387 publications
(202 citation statements)
references
References 167 publications
(206 reference statements)
12
188
0
2
Order By: Relevance
“…Venlafaxine, a serotonin-norepinephrine reuptake inhibitor (NSRI) that controls equally depression and chronic pain [31, 32] was selected to combine clonazepam. Venlafaxine inhibits serotonin and norepinephrine reuptake leading to enhanced descending inhibition of centrally sensitized pain and has been used to treat pain conditions comorbid with depression [33].…”
Section: Discussionmentioning
confidence: 99%
“…Venlafaxine, a serotonin-norepinephrine reuptake inhibitor (NSRI) that controls equally depression and chronic pain [31, 32] was selected to combine clonazepam. Venlafaxine inhibits serotonin and norepinephrine reuptake leading to enhanced descending inhibition of centrally sensitized pain and has been used to treat pain conditions comorbid with depression [33].…”
Section: Discussionmentioning
confidence: 99%
“…37 As an aside, it is interesting to note that the coexpression of pain and depression reflects the spinofugal pathways activated during chronic pain, which project to higher-order systems responsible for not only the sensory discriminative but also the affective-motivational component of a chronic pain phenotype. 24 , 40 , 51 Indeed, the negative impact of the synergistic effect of the pain-depression complex, as well as other psychological conditions, such as anxiety and pain catastrophizing (PC), during perioperative stages in patients waiting for TKA surgeries has been described. 19 , 31 , 39 , 58 Lingard et al (2004) reported that mental health status, among other preoperative variables, was associated with poor functional outcome and persistent pain after TKA.…”
Section: Effects Of Delayed Surgical Repair On Comorbiditiesmentioning
confidence: 99%
“…Individuals with chronic pain often present with comorbid mental health problems including depression, anxiety, substance use and personality disorders (Dersh, Polatin, & Gatchel, 2002), and most commonly with high levels of depression and anxiety (Demyttenaere et al, 2007;Hooten, 2016). There is now a growing body of evidence which finds high rates of comorbidity between chronic pain, traumatic exposure and post-traumatic stress disorder (PTSD), including in individuals seeking treatment for chronic pain (Fishbain, Pulikal, Lewis, & Gao, 2017;Siqveland, Hussain, Lindstrøm, Ruud, & Hauff, 2017).…”
Section: Introductionmentioning
confidence: 99%